Keragaman dan sebaran spasial kupu-kupu (Lepidoptera: Rhopalocera) pada ruas jalan Jantho-Lamno di Kecamatan Cot Glie - Yaumil Ma’arif; Yekki Yasmin; Irvianty Irvianty; Cut Nanda Devira; Zuriana Siregar; Suwarno Suwarno (Universitas Syiah Kuala, 2024)
Butterflies are distributed in various types of habitats and can be used as bioindicators of environmental quality. Landscape changes can affect the diversity and composition of butterflies. An inventory of butterflies (Lepidoptera: Rhopalocera) in several habitat types on the Jantho-Lamno Route, Aceh Besar, has been carried out with the aim of determining the diversity and composition of species as well as their spatial distribution. Butterfly samples were collected directly in five types of habitats, namely river streams, forests, plantations, bushes, and burnt land, located around the Jantho-Lamno road, in the administrative area of Cot Glie District, Aceh Besar Regency. A total of four sampling points were determined for each habitat type, with each point being 1 ha in area and a minimum distance of 1 km. The research results obtained were 52 species and 5 families. The butterflies that were most commonly found were the Nymphalidae family with 31 species (69.85%), followed by Papilionidae with 9 species (17.12%), and the fewest were Hesperiidae with 1 species (0.63%). The diversity index is classified as high, namely H'=3.795. A total of 38 of the 52 species of butterflies found were distributed in forest habitats, 33 species in bush habitats, 31 species in burnt land, 30 species in rivers, and 19 species in gardens. The Nymphalidae and Papilionidae are distributed in all habitat types, but are found more often in forests and bushes. Meanwhile, the Lycaenidae are only found in riverbank and forest habitats, the Pieridae in forests and gardens, and the Hesperidae only in forest habitats. The common food plants found at the research location were Lantana camara, Eupatorium inulifolium, and Clibadium surinamense.